PENYULUHAN HUKUM UNTUK MENINGKATKAN KESADARAN TENTANG BAHAYA KENAKALAN REMAJA DAN AKIBAT HUKUMNYA PADA SISWA SMA 8 KENDARI - Yusuf , Niken Yulian; Yusuf, Virya Suprayogi; Supriadi, Supriadi; Yusuf, M; Kurniawati, Wa Ode Intan; Hariru, La Ode; Faisal, Amir; Ismail, La Ode; Putri, Sri; Akmal, Akmal (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Juvenile delinquency is a social problem that often occurs among students, including in Kendari City. This is an important concern considering the negative impacts that can be caused, both for individuals and society. One way to overcome these problems is to provide legal counseling to students, especially at SMA 8 Kendari. This legal counseling activity includes material on various forms of juvenile delinquency, such as fighting, theft, and drug abuse, as well as applicable legal sanctions in accordance with existing laws and regulations. The results of this activity are expected to form a wiser student mindset in dealing with various social problems and reduce the number of juvenile delinquency among students. In addition, this counseling can also strengthen students' understanding of the role of law in creating a safe and orderly environment. Thus, through legal counseling, SMA 8 Kendari students are expected to become agents of change in reducing juvenile delinquency in their environment.